Implementasi KMA No. 183 Tahun 2019 pada Pembelajaran PAI di MTs N Salatiga dan MTs NU Ungaran Kabupaten Semarang - Baiti, Desi Nur; Miftahuddin, Miftahuddin (CV. Creative Tugu Pena, 2022)
This study aims to find out how (1) the concept of PAI curriculum development in KMA no. 183 of 2019 (2) Implementation of KMA 183 of 2019 in PAI learning at MTs Negeri Salatiga and MTs NU Ungaran Kab.Semarang (3) supporting factors and inhibiting factors in implementing KMA 183 in PAI learning at MTs N Salatiga and MTs NU Ungaran Kab.Semarang.This type of research uses a qualitative approach. The data collection techniques in this study were by means of observation, interviews and documentation. The results show that the concept of developing the PAI curriculum in KMA no. 183 of 2019 is to prepare Indonesian people to have a moderate, inclusive, cultured, religious mindset and attitude and have the ability to live as individuals and citizens who are faithful, pious, and have noble character. Implementation has been implemented with the following steps: (1) Designing of the PAI curriculum in accordance with KMA 183 in 2019 starting from KTSP, RPP, Syllabus, PROTA, PROMES, (2) Implementing, by utilizing Information and Communication Technology in PAI learning and fulfilling references to teaching materials from various sources as well as innovations made by PAI teachers (3) Assessment of learning outcomes by improving question level, becomes a HOTS question. There are supporting factors namely: First, the existence of teacher organizations such as the MGMP (Subject Teacher Conference) at the city/district level. Second, the facilities and teaching aids in the madrasa that support the PAI learning process. Third, the e-book of PAI teaching materials from the Ministry of Religion Keywords: Implementation KMA, Curriculum Development, Curriculum Islamic Education